Weerklank op het werk van Jan Romein : liber amicorum - Pos, H.J. (Amsterdam: Wereldbibliotheek; Antwerpen, 1953)
"onder redactie van het werkcomité: Prof. Dr H.J. Pos, Dr O. Noordenbos, Prof. Dr B. Becker, Prof. Dr J. Presser, Prof. H. Schulte Nordholt"